동 테르밋 용접 특성 향상을 위한 폐 산화동 분말 입도 제어 연구 - 이한성; 김민수; 안병민 (한국분말재료학회지, 2023)
Thermite welding is an exceptional process that does not require additional energy supplies, resulting in welded joints that exhibit mechanical properties and conductivity equivalent to those of the parent materials. The global adoption of thermite welding is growing across various industries. However, in Korea, limited research is being conducted on the core technology of thermite welding. Currently, domestic production of thermite powder in Korea involves recycling copper oxide (CuO). Unfortunately, controlling the particle size of waste CuO poses challenges, leading to the unwanted formation of pores and cracks during thermite welding. In this study, we investigate the influence of powder particle size on thermite welding in the production of Cu-thermite powder using waste CuO. We conduct the ball milling process for 0.5–24 h using recycled CuO. The evolution of the powder shape and size is analyzed using particle size analysis and scanning electron microscopy (SEM). Furthermore, we examine the thermal reaction characteristics through differential scanning calorimetry. Additionally, the microstructures of the welded samples are observed using optical microscopy and SEM to evaluate the impact of powder particle size on weldability. Lastly, hardness measurements are performed to assess the strengths of the welded materials.
Keywords: Thermite welding; Milling time; Recycled copper oxide; Microstructure; Copper thermite